Cilia-Localized Counterregulatory Signals as Drivers of Renal Cystogenesis - Walker, Rebecca V.; Maranto, Anthony; Palicharla, Vivek Reddy; Hwang, Sun-Hee; Mukhopadhyay, Saikat; Qian, Feng (Frontiers in Molecular Biosciences, 2022)
Primary cilia play counterregulatory roles in cystogenesis—they inhibit cyst formation in the normal renal tubule but promote cyst growth when the function of polycystins is impaired. Key upstream cilia-specific signals and components involved in driving cystogenesis have remained elusive. Recent studies of the tubby family protein, Tubby-like protein 3 (TULP3), have provided new insights into the cilia-localized mechanisms that determine cyst growth. TULP3 is a key adapter of the intraflagellar transport complex A (IFT-A) in the trafficking of multiple proteins specifically into the ciliary membrane. Loss of TULP3 results in the selective exclusion of its cargoes from cilia without affecting their extraciliary pools and without disrupting cilia or IFT-A complex integrity. Epistasis analyses have indicated that TULP3 inhibits cystogenesis independently of the polycystins during kidney development but promotes cystogenesis in adults when polycystins are lacking. In this review, we discuss the current model of the cilia dependent cyst activation (CDCA) mechanism in autosomal dominant polycystic kidney disease (ADPKD) and consider the possible roles of ciliary and extraciliary polycystins in regulating CDCA. We then describe the limitations of this model in not fully accounting for how cilia single knockouts cause significant cystic changes either in the presence or absence of polycystins. Based on available data from TULP3/IFT-A-mediated differential regulation of cystogenesis in kidneys with deletion of polycystins either during development or in adulthood, we hypothesize the existence of a cilia-localized component of CDCA (cCDCA) and cilia-localized cyst inhibition (CLCI) signals. We develop the criteria for cCDCA/CLCI and discuss potential TULP3 cargoes as possible components of the cilia-localized signals that determine cystogenesis in kidneys during development and in adult mice.